Ragam Liken Berdasarkan Ketinggian Dataran sebagai Bioindikator Kualitas Ekosistem di Cagar Alam Rawa Danau Serang Banten - Rida Oktorida Khastini; Indah Juwitasari; Siti Sulasanah (Universitas Islam Negeri Mataram, 2018)
Lichen is a symbiotic organism, made up of two or more different organisms living together. Lichen biodiversity may provide an excellent system in bio-monitoring of the ecosystem health of nature reserve areas such as Rawa Danau in Banten Province, Indonesia. The study on lichen diversity was conducted on Rawa Danau based on altitude using transect based plot in three main habitats based on altitude e.g. 90 mbsl, 100-130 mbsl, 130-160 mbsl, 160-187 mbsl. A total 63 specimens were collected from these four areas which resulted in the occurrence of 19 species of lichens belonging to 17 genera and 13 families. Shannon–Winner’s diversity index from 1.494 to 2.6678. The variation in species composition was related to the environmental habitat variables and lichens demonstrated a condition of environmental alteration.